Building sustainable peace for development among muslims and non-muslims in Bida emirate: an effective strategy for Nigeria (2010)
While many parts of the world have experienced conflicts and war, Bida Emirate remains a cauldron of stability and peace. Many research works have examined causes and impacts of conflicts in many parts of the world and socio-political and economic activities in Nupe with scant attention to the causes of peaceful Operational environment in Bida Emirate. Therefore, this study examines the determinants of peace in the study area which is multi-religious and has different ethnic affiliations. The researchers used purposive sampling technique and conducted in depth interviews with the people at the helms of affairs in Bida Emirate such as Etsu Nupe, chief Imams, the leaders of Christian Association of Nigeria and ethnic groups, some individuals and law enforcement agents for their roles in achieving sustainable peace. The study revealed that Etsu Nupe used his position as the royal father to prevent, manage and settle conflicts and minor misunderstandings among his people before they degenerated into significant violence. Findings also showed that annual inter-sect gatherings in Etsu Nupe’s palace, dialogue, justice, tolerance, understanding of the Qur’an and the Sunnah of Prophet Muhammad (PBUH) and guidelines of Jamat Nasrul Islam on issues such assiting of central mosques and takfiir (calling a person an unbeliever) fasclitated sustainable peace there. Prevention is used to keep Bida Emirate safe from ethnoreligious and political conflicts; and this saves human and natural resources. Muslim and Christian preachers should intensify their preaching towards godliness, tolerance, patience, love of others and respect for elders and to one another.